Colorectal Cancer Cell-Derived Extracellular Vesicles Promote Angiogenesis Through JAK/STAT3/VEGFA Signaling - Yuqing Long; Yuxi Dan; Yao Jiang; Jing Ma; Tao Zhou; Liaoqiong Fang; Zhibiao Wang (Biology)
Background: Angiogenesis plays a crucial role in the growth of colorectal cancer (CRC). Recent studies have identified extracellular vesicles (EVs) in the tumor microenvironment as important mediators of cell-to-cell communication. However, the specific role and mechanisms of CRC-derived EVs in regulating tumor angiogenesis remain to be further investigated. Methods: EVs were isolated from the conditioned medium of the CRC cells using ultracentrifugation. We investigated the effects of HT-29-derived EVs on tumor growth and angiogenesis in a subcutaneous HT-29 CRC tumor model in mice. Additionally, we evaluated the impact of HT-29-derived EVs on the proliferation, migration, and tube formation of human umbilical vein endothelial cells (HUVECs). Subsequently, bioinformatics analysis was performed to identify relevant signaling pathways, and pathway inhibitors were used to block the activation of these pathways, aiming to elucidate their roles in angiogenesis. Results: We found that HT-29-derived EVs can promote tumor growth and angiogenesis in vivo, as well as significantly enhance the proliferation, migration, and tube formation of HUVECs. Bioinformatics analysis revealed that HT-29-derived EVs may regulate angiogenesis through the JAK/STAT3 signaling pathway. Specifically, we observed that CRC-derived EVs promoted the phosphorylation of STAT3 (p-STAT3) and the expression of VEGFA in the nucleus of HUVECs. Treatment with the STAT3 inhibitor Stattic reduced the nuclear expression of p-STAT3, which impaired its function as a transcription factor, thereby inhibiting VEGFA expression and the pro-angiogenic effects of CRC-derived EVs. Conclusions: EVs derived from CRC cells promote CRC tumor angiogenesis by regulating VEGFA through the JAK/STAT3 pathway in endothelial cells.